Pengembangan Modul Pembelajaran Bahasa Arab Berbasis Pendidikan Karakter - Hidayatullah, Muhammad Subkhi; Gunawan, Riski (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
The current state of the character development among the nation's youth is facing challenges, including issues such as juvenile delinquency and bullying. These problems are particularly prevalent among adolescents in middle school and above. Therefore, there is a need for attention from educational practitioners to address and actively engage in improving this situation, including those studying Arabic. Among the various efforts to instill character in Arabic language learning is the development of character-based Arabic language teaching materials. This research aims to address these issues by developing a module as a relevant instructional material capable of accommodating the cultivation of character values while supporting Arabic language learning. The method employed in this research is the research and development approach using the ADDIE model, consisting of four stages: Analysis, Design, Development, Implementation, and Evaluation. The results of this research indicate that the developed module falls into the category of highly valid, with expert material validation scoring 3.803 and media expert validation scoring 4.65, both criteria being considered excellent and worthy of continuation. Students' responses to the Arabic language learning module yielded an average score of 4.148, indicating a very good and engaging criteria